Influence of foliar nutrition on apple production - Stampar, F.; Solar, A.; Hudina, M. (International Journal of Horticultural Science, 2003)
On the basis of different experiments the technology of intensive foliar nutrition was studied in apple orchards in the period from 1996 until 2000. Yearly apple nutrition programs based on soil analyses. The foliar nutrition program was prepared in accordance with the soil, fruit analyses and climatic conditions. If needed, certain improvements were made according to the analyses of leaves and precipitation in the current year. The richness of the soil and ratios between individual nutrients gradually improved. The foliar nutrition influenced the yield quantity, quality and flower bud differentiation. The yield was doubled and the mean of five years reached 70 tons per hectare. In spite of high yields there were no problems with alternative bearing. The analyses of soluble solids, firmness, fructose, glucose, sucrose, malic acid, citric acid in the fruits and mineral soil composition indicated that the produced fruits were of high quality despite greater yields.